2019
DOI: 10.1108/md-11-2017-1195
|View full text |Cite
|
Sign up to set email alerts
|

A network view of entrepreneurial cognition in corporate entrepreneurship contexts

Abstract: Purpose Research in entrepreneurial cognition has called for a better understanding of interactions between contextual variables and cognitive processes. Based on previous work done on organizational learning and social networks, the purpose of this paper is to propose a formal model in which information acquisition, distribution and interpretation are tested as a function of cognition-based trust, perceived expertise and tie strength between organizational members in two different corporate entrepreneurship (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Taken as a whole, these results suggest that the lens of “entrepreneurial cognition” (Corbett and Hmieleski, 2007; Garrett and Holland, 2015; Mitchell et al , 2002; Thomas et al , 2019) may be usefully used by empirical studies on corporate entrepreneurship. While some conceptual publications exist that consider how cognitions may differ between independent entrepreneurs and corporate entrepreneurs (e.g.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Taken as a whole, these results suggest that the lens of “entrepreneurial cognition” (Corbett and Hmieleski, 2007; Garrett and Holland, 2015; Mitchell et al , 2002; Thomas et al , 2019) may be usefully used by empirical studies on corporate entrepreneurship. While some conceptual publications exist that consider how cognitions may differ between independent entrepreneurs and corporate entrepreneurs (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…(2019) also describes how search versus execution behaviors in entrepreneurial firms might be affected by cognitive approaches. While some research has also explored the cognitions of corporate entrepreneurs (e.g., Corbett and Hmieleski, 2007; Garrett and Holland, 2015; Thomas et al ., 2019), there is yet a link lacking between these cognitions and actual decision-making behaviors of corporate entrepreneurs. A better understanding of the decision-making schemas used by corporate entrepreneurs would contribute much to our understanding of how corporate entrepreneurs differ from independent entrepreneurs and what attributes of ICV context are salient to corporate entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of their behavioral intention further determines their actual purchase behaviors. Thomas et al (2019) investigated the Indian enterprises in terms of social network, organizational learning and organizational cognition by taking the attitude as moderating effect. The research results showed that, according to the Multiple Regression Analysis (MRA), social network is strongly associated with the organizational learning, social network is interactive with the organization cognition, and the organizational cognition has positive effects on the attitude.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Clarke and Cornelissen (2011) operationalized cognition in entrepreneurship by locating it in the context of language and sense-making. More recent studies expand the social cognition perspective in the context of cross-country entrepreneurial activity (Raza et al, 2018) or networks (Thomas et al, 2019) where relationships are complex and extend beyond organizational and cultural boundaries. These studies confirm that a social cognition perspective in entrepreneurship creates opportunities to combine cognitive, motivational, and emotional forces in various social contexts (Mitchell et al, 2011).…”
Section: Creativity and Entrepreneurial Intentionmentioning
confidence: 99%